PERTUMBUHAN BIJI KAKAO (Theobroma cacao L.) TERHADAP BEBERAPA LAMA PERENDAMAN DENGAN DAGING BUAH DAN TANPA DAGING BUAH - Dede Suhendra (UNIVERSITAS LABUHANBATU, 2019)
The objective of testing some cocoa seed germination methods is to obtain information on growing ability based on sprout speed, sprout test, and vigilance. Seed germination is also influenced by the long immersion in water, the longer the soaking time germination will also be faster. The purpose of this research is to know the growth of cocoa beans to sometime soaking with fruit flesh and without meat. This research was conducted at the Laboratory of College of Agricultural Sciences of Labuhan Batu University Foundation, North Sumatera Province. This research started from March to May 2016, using factorial randomized block design with 2 factors of treatment that is the long factor of immersion and flesh factor. The old factors of immersion with 6 levels are: P1 = 2 hours, P2 = 4 hours, P3 = 6 hours, P4 = 8 hours, P5 = 10 hours, P6 = 12 hours. Factor of fruit with two levels, namely: using fruit and fruitless meat. Parameters observed included shoot number, shoot height (cm), root length (cm), wet weight of germination (g), and sprout dry weight (g). The results showed that the method of soaking the seeds was effective to increase the sprout growth rate without affecting the viability of the cocoa sprouts. Keywords: cocoa, long immersion.